2004
DOI: 10.1039/b303308b
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-Rayleigh scattering of gold nanorods and their relationship with linear assemblies of gold nanospheres

Abstract: The surface plasmon enhanced hyper-Rayleigh scattering light collected from an aqueous solution of gold nanorods is reported. A non negligible part of the signal is attributed to a photoluminescence background attributed to the electron-hole recombination following multiphoton excitation of d-valence band electrons into the sp-conduction band. This radiative relaxation process is likely favored by the presence of the organic species adsorbed at the surface of the nanorods. The absolute value for the hyperpolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…The HRS technique [19][20][21][22][23][24][25][26][27][28][29][30] is based on light scattering. The intensity of the Rayleigh scattering is linearly dependent on the number density and the impinging laser intensity, and quadratically on the linear polarizability α.…”
Section: Spectroscopy Of Nanoscale Interfacementioning
confidence: 99%
See 4 more Smart Citations
“…The HRS technique [19][20][21][22][23][24][25][26][27][28][29][30] is based on light scattering. The intensity of the Rayleigh scattering is linearly dependent on the number density and the impinging laser intensity, and quadratically on the linear polarizability α.…”
Section: Spectroscopy Of Nanoscale Interfacementioning
confidence: 99%
“…This enhancement factor is comparable with the SERS signal enhancement [1][2][3][4] . In fact, it has been shown that [19][20][21][22][23][24][25][26] the HRS technique is considerably more sensitive than 1) the normal Rayleigh scattering, the typical spectroscopic technique to monitor nanoparticle aggregate size and 2) the absorption spectroscopy, because it responds to the to the formation of smaller particle aggregates; thus the onset of the HRS enhancement should be observable before any visible color change occurs. Therefore, one can use this HRS technique to probe target molecules coated onto nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations